2006
DOI: 10.1021/jp065255z
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Photocatalytic Decomposition of Amino Acids in TiO2 Photocatalytic Systems

Abstract: The adsorption and photodecomposition of seven kinds of amino acids on a TiO2 surface were investigated by zeta potential measurements and 1H NMR spectroscopy in TiO2 aqueous suspension systems. The decomposition rates increased in the order of Phe < Ala < Asp < Trp < Asn < His < Ser. For Phe, Trp, Asn, His, and Ser, the isoelectric point (IEP) of TiO2 shifted to a lower pH with increasing decomposition rates upon adsorption on TiO2, suggesting that the effective adsorption and photocatalytic sites for these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 32 publications
4
62
0
1
Order By: Relevance
“…The specific interactions between TiO 2 particles and proteins are not well understood. Studies have revealed that TiO 2 particles have a net negative charge (at pH = 7) [44] and also bind preferentially to amino acids containing -OH, -NH, and -NH 2 in their side chains [45]. These observations indicate that TiO 2 particles may react with cell membrane proteins and contribute to cell:particle interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The specific interactions between TiO 2 particles and proteins are not well understood. Studies have revealed that TiO 2 particles have a net negative charge (at pH = 7) [44] and also bind preferentially to amino acids containing -OH, -NH, and -NH 2 in their side chains [45]. These observations indicate that TiO 2 particles may react with cell membrane proteins and contribute to cell:particle interaction.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the bridged OH groups have greater thermodynamic stability than terminal OH groups. 29 Since the bridging hydroxyl is acidic (pKa 2.9), whereas the terminal hydroxyl is basic (pKa 12.7), 30,31 generation of more bridging hydroxyls at pH 5.40 would contribute more negative charges and reduce the overall positive charge on TiO 2 as observed in EPM measurement. This is consistent with the above DLVO calculations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As can be seen, the isoelectric points (IEP), i. e., the pH for which the surface charge is balanced, , which are in the range of the ones previously reported in the literature(20)(21)(22), indicate the point where the electrostatic repulsion does not contribute to the colloidal stability. It is assumed that at highly negative or positive values of ζ potential,…”
mentioning
confidence: 74%